The influenza A virus NS genome segment displays lineage-specific patterns in predicted RNA secondary structure. (December 2016) - Vasin, A.; Petrova, A.; Egorov, V.; Plotnikova, M.; Klotchenko, S.; Karpenko, M.; Kiselev, O.
Abstract Background Influenza A virus (IAV) is a segmented negative-sense RNA virus that causes seasonal epidemics and periodic pandemics in humans. Two regions (nucleotide positions 82–148 and 497–564) in the positive-sense RNA of the NS segment fold into a multi-branch loop or hairpin structures. Results We studied 25, 384 NS segment positive-sense RNA unique sequences of human and non-human IAVs in order to predict secondary RNA structures of the 82–148 and 497–564 regions using RNAfold software, and determined their host- and lineage-specific distributions. Hairpins prevailed in avian and avian-origin human IAVs, including H1N1pdm1918 and H5N1. In human and swine IAV hairpins distribution varied between evolutionary lineages. Conclusions These results suggest a possible functional role for these RNA secondary structures and the need for experimental evaluation of these structures in the influenza life cycle.